A polêmica mudança na partilha das receitas petrolíferas - Sérgio Wulff Gobetti; Rodrigo Octávio Orair; Rodrigo Valente Serra; Fernando Gaiger Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper aims at contributing to the debate on the socioeconomic (and constitutional) relevance of the changes in the distribution of oil royalties prescribed at the Law 12.734/2012, whose effects are currently suspended by an injunction granted by the Supreme Court. The research shows that the confrontation criteria for offshore oil revenue sharing to states and municipalities is unusual at international level and lacks socioeconomic logic, being the result of political bargains. Furthermore, the paper discusses evidence that the hyperconcentration of revenues, in addition to being unfair, is inefficient in socioeconomic and fiscal terms. The paper provides arguments in favour of increasing the share of revenues divided among all entities of the Federation through the special oil fund, such as foreseen in Law 12.734/2012.
Keywords: H27; H77; Q38; 330; oil royalties; oil revenues; fiscal federalism